2007
DOI: 10.1149/1.2734862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NiB, PbO, and TiO[sub 2] on SCC of Sensitized Inconel Alloy 600 in RT-Tetrathionate Solution

Abstract: The effects of NiB, PbO, and TiO 2 additives ͑impurities͒ on stress corrosion cracking ͑SCC͒ of sensitized alloy 600 were investigated in 0.1 M Na 2 S 4 O 6 solution using potentiodynamic polarization experiment, electrochemical impedance spectroscopy, and electrochemical noise measurement. From the analysis of the electrochemical noises based upon the shot-noise theory, the induction time for stress corrosion ͑SC͒ crack initiation was quantitatively determined. Furthermore, SC crack propagation was satisfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, Pyun et al reported that the value of m increases from 0.7 up to unity with a decreasing applied potential (Pyun et al, 1993) for the pit generation at the surface of Al alloy at room temperature, and the value of m decreases from 0.4 to 0.1 with the addition of SO 4 2-and MoO 4 2-ions in a 0.1 M NaCl solution (Na et al, 2007a) and with the addition of SO 4 2-, NO 3-and PO 4 3-ions in a 1M HCl solution (Na & Pyun, 2007) for the pit initiation at the surface of pure Al at room temperature. Interestingly, they also reported that the value of m is 0.33 for the SCC propagation of Alloy 600 in a neutral solution containing PbO at room temperature (Na et al, 2007b). In our previous works (Kim & Kim, 2009a;Na et al, 2007a;Na et al, 2007b), it was reported that the shape parameter m of the Weibull distribution can be regarded as an indicator of types of corrosion.…”
Section: Stochastic Analysis Of Electrochemical Noisementioning
confidence: 96%
See 4 more Smart Citations
“…On the other hand, Pyun et al reported that the value of m increases from 0.7 up to unity with a decreasing applied potential (Pyun et al, 1993) for the pit generation at the surface of Al alloy at room temperature, and the value of m decreases from 0.4 to 0.1 with the addition of SO 4 2-and MoO 4 2-ions in a 0.1 M NaCl solution (Na et al, 2007a) and with the addition of SO 4 2-, NO 3-and PO 4 3-ions in a 1M HCl solution (Na & Pyun, 2007) for the pit initiation at the surface of pure Al at room temperature. Interestingly, they also reported that the value of m is 0.33 for the SCC propagation of Alloy 600 in a neutral solution containing PbO at room temperature (Na et al, 2007b). In our previous works (Kim & Kim, 2009a;Na et al, 2007a;Na et al, 2007b), it was reported that the shape parameter m of the Weibull distribution can be regarded as an indicator of types of corrosion.…”
Section: Stochastic Analysis Of Electrochemical Noisementioning
confidence: 96%
“…Interestingly, they also reported that the value of m is 0.33 for the SCC propagation of Alloy 600 in a neutral solution containing PbO at room temperature (Na et al, 2007b). In our previous works (Kim & Kim, 2009a;Na et al, 2007a;Na et al, 2007b), it was reported that the shape parameter m of the Weibull distribution can be regarded as an indicator of types of corrosion. In the present work, the value of m determined from Fig.…”
Section: Stochastic Analysis Of Electrochemical Noisementioning
confidence: 96%
See 3 more Smart Citations